Effect of Applying Cold Plasma on Structural, Antibacterial and Self Cleaning Properties of α-Fe2O3 (HEMATITE) Thin Film - Abdalhussain A. Khadayeir; Ahmed H. Wannas; Falah H. Yousif (Emerging Science Journal, 2022)
Objective: In this study, α-Fe2O3 thin film was formed on a glass substrate to study the impact of adding cold plasma on the self-cleaning and antibacterial properties of the samples. Method: The samples were synthesized using the chemical spray pyrolysis (CSP) method at 450°C. X-ray powder diffraction (XRD), scanning electron microscope (FESEM), energy-dispersive X-ray spectroscopy (EDS), and atomic force microscope were used to investigate the morphological and structural characteristics of α-Fe2O3 thin layers prior to and following plasma injection. Finding: The degree of wettability and antibacterial characteristics of iron oxide (hematite) thin film were evaluated in the presence of gram-negative and gram-positive bacteria prior to and following plasma injection, given the great potential of plasma injection in the surface modification of thin films. Novelty: The findings indicate that exposing plasma to α-Fe2O3thin film produces substantial changes in morphology, self-cleaning, and antibacterial characteristics. Doi: 10.28991/ESJ-2022-06-01-06 Full Text: PDF